Epidemiology of sudden death in organized youth sports in the United States, 2007-2015 - Endres, B. D.; Kerr, Z. Y.; Stearns, R. L.; Adams, W. M.; Hosokawa, Y.; Huggins, R. A.; Kucera, K. L.; Casa, D. J. (Journal of Athletic Training, 2019)
Context Sudden death in sport at the high school and collegiate levels has been described extensively in the literature. However, few epidemiologic data exist on the incidence of sudden death specifically in American youth sport before secondary school athletics.